Effects of sugar types and organic acids used on heterocylic amines (HCAs) formation in marinated chicken satay - Hasnol, Nur Diyana Syamim (2014)
The aim of the study was first to determine the effect of different types of sugar as marinating ingredients on the formation of heterocyclic amines in grilled chicken (satay). Table sugar, brown sugar, and honey were used. Internal temperature and weight loss of the grilled chicken were measured. HCA precursors (free amino acids and sugar concentration) were determined before and after marinating. HCA were quantified using Liquid Chromatography-Mass Spectrometry (LCMS) with triple quadrupole mass analyzer. The mean internal temperature of the grilled chicken marinated with table sugar, brown sugar, and honey were 82.3°C, 82.3°C, and 82.3°C, respectively and was not significant different (p > 0.05) with each other. Mean percentage of weight loss of the grilled chicken was significantly (p < 0.05) lower for marinades with honey (35%) than with table sugar (37%), and with brown sugar (38%). There was no significant difference (p > 0.05) in the means between treatments and control samples for amino acids. The mean concentration of fructose and glucose in chicken samples using honey marinades was found to be 3.89 and 3.68 g/100 g, respectively, and this was significantly higher (p < 0.05) than with brown sugar (0.70 and 1.58 g/100 g), and with table sugar (0.65 and 1.60 g/100 g, respectively). In the present study, glucose was the only sugar detected in the control samples (0.67 g/100 g). The mean concentration of sucrose was significantly (p < 0.05) higher in chicken samples that were marinated with table sugar (12.8 g/100 g) than those with brown sugar (8.6 g/100 g), and with honey (0.43 g/100 g). When honey was used as one of the ingredients, substantial reductions in the concentration of MeIQ, DiMeIQx, IQ, IQx, and Norharman in grilled chicken were achieved. Moreover, a correlation study has indicated that when honey was added into the recipe, the formation of most HCA (i.e., MeIQ, DiMeIQx, IQ, IQx, Norharman, and Harman) was reduced while some other HCA (i.e., PhIP, MeIQx, and AαC) increased in concentration. In addition, table sugar showed a strong correlation in enhancing the formation of all HCA except for Norharman, Harman, and AαC. To minimize the formation of HCA, the present study recommends using honey to partially replace the table sugar for the purpose of giving a sweet taste in the marinated grilled meat. The second objective was to study the use of other alternative organic acids in formulating marinating ingredients to reduce HCA in grilled chicken (satay). Chicken breast samples were marinated with table sugar, brown sugar, and honey with the addition of organic acid (tamarind, lemon, lime, and calamansi) for 24 hrs at 4°C. The pH before and after marinating were measured. HCA concentrations before and after grilling were quantified. There was a significant difference (p < 0.05) in the combined dependent variables (for all HCA) among the control and marinated grilled chickens. Using lemon in marinades containing table sugar, the high concentrations of DiMeIQx significantly reduced (p < 0.006) from 16.5 ng/g for low concentration to 8.30 ng/g for high concentration of organic acid ingredients. Similarly, in marinades containing brown sugar, the high concentrations of DiMeIQx significantly reduced (p < 0.006) from 35.0 ng/g for low concentration to 16.2 ng/g for high concentration of organic acid ingredients. It was observed that for all types of sugars, the mean pH of the treated samples was lower than those in the control samples. For marinades containing table sugar, the pH of chicken samples was 5.14 for tamarind, 5.28 for lemon, 5.24 for lime, and 4.94 for calamansi: these pH were significantly lower (p < 0.05) than those of control samples (5.48). The reduction was 57% for IQx, for MeIQx by 82%, for IQ by 61%, for DiMeIQx by 80%, and for MeIQ by 71%. Also, when calamansi was added at high concentration in marinades containing brown sugar, substantial reduction in the concentration was high; 64% for IQx and IQ, for DiMeIQx by 70 %, except for MeIQx, in which the concentrations were increased by 44 %. The highest percentage of reductions was achieved when tamarind was added at high concentration in marinades containing honey. The concentrations were reduced for IQx by 90 %, for MeIQx by 67 %, for IQ by 81 %, for DiMeIQx by 88 %, for MeIQ by 74 % and for PhIP by 76 %. High percentage of reduction was also achieved for Norharman (63 %), and AαC (81 %). Calamansi was found to reduce HCA in marinades containing table sugar and brown sugar, whereas tamarind in marinades containing honey.